Prayer and Wisdom on the Board of on Environmental Cleaning Warnings: Functions and Meaning - Ira Mayasari (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study was to determine the function of language and affective meaning on environmental hygiene warning boards. This research is a qualitative descriptive study, namely by analyzing writing data on environmental hygiene warning boards. The object of this research is written data on the father of environmental hygiene warnings taken from the internet. The conclusions from the results of the study are that there are three language functions, namely informational, expressive, and directive functions. From 42 data, there are 13 informational functions, 14 expressive functions, and 15 directive functions. Based on the meaning, 13 positive affective meanings and 28 negative affective meanings were found.